American-Sino OB/GYN/Pediatrics Services (ASOG), Shanghai Business Plan 2012-16 - Ding, Haohong; Jacob, Mathew (2012)
The sincere support from the Management leadership is highly appreciated for providing the fundamental operating information and knowledge on the professional industry technologies. The business plan analyses the current situation of ASOG, the trends of OB/GYN industry and customers’ needs. The results are further narrowed down to frame the mission and vision statements, identify a new strategy, develop and suggest implementing the feasible tactics that will lead the sustainable development.